Exploring the multifaceted role of obesity in breast cancer progression - Kakkat, Sooraj; Suman, Prabhat; Turbat- Herrera, Elba A.; Singh, Seema; Chakroborty, Debanjan; Sarkar, Chandrani (Frontiers in Cell and Developmental Biology, 2024)
Obesity is a multifaceted metabolic disorder characterized by excessive accumulation of adipose tissue. It is a well-established risk factor for the development and progression of breast cancer. Adipose tissue, which was once regarded solely as a passive energy storage depot, is now acknowledged as an active endocrine organ producing a plethora of bioactive molecules known as adipokines that contribute to the elevation of proinflammatory cytokines and estrogen production due to enhanced aromatase activity. In the context of breast cancer, the crosstalk between adipocytes and cancer cells within the adipose microenvironment exerts profound effects on tumor initiation, progression, and therapeutic resistance. Moreover, adipocytes can engage in direct interactions with breast cancer cells through physical contact and paracrine signaling, thereby facilitating cancer cell survival and invasion. This review endeavors to summarize the current understanding of the intricate interplay between adipocyte-associated factors and breast cancer progression. Furthermore, by discussing the different aspects of breast cancer that can be adversely affected by obesity, this review aims to shed light on potential avenues for new and novel therapeutic interventions.